Beyond Genetics: The Role of Metabolism in Photoreceptor Survival, Development and Repair - Hanna, Joseph; David, Luke Ajay; Touahri, Yacine; Fleming, Taylor; Screaton, Robert A.; Schuurmans, Carol (Frontiers in Cell and Developmental Biology, 2022)
Vision commences in the retina with rod and cone photoreceptors that detect and convert light to electrical signals. The irreversible loss of photoreceptors due to neurodegenerative disease leads to visual impairment and blindness. Interventions now in development include transplanting photoreceptors, committed photoreceptor precursors, or retinal pigment epithelial (RPE) cells, with the latter protecting photoreceptors from dying. However, introducing exogenous human cells in a clinical setting faces both regulatory and supply chain hurdles. Recent work has shown that abnormalities in central cell metabolism pathways are an underlying feature of most neurodegenerative disorders, including those in the retina. Reversal of key metabolic alterations to drive retinal repair thus represents a novel strategy to treat vision loss based on cell regeneration. Here, we review the connection between photoreceptor degeneration and alterations in cell metabolism, along with new insights into how metabolic reprogramming drives both retinal development and repair following damage. The potential impact of metabolic reprogramming on retinal regeneration is also discussed, specifically in the context of how metabolic switches drive both retinal development and the activation of retinal glial cells known as Müller glia. Müller glia display latent regenerative properties in teleost fish, however, their capacity to regenerate new photoreceptors has been lost in mammals. Thus, re-activating the regenerative properties of Müller glia in mammals represents an exciting new area that integrates research into developmental cues, central metabolism, disease mechanisms, and glial cell biology. In addition, we discuss this work in relation to the latest insights gleaned from other tissues (brain, muscle) and regenerative species (zebrafish).